2012
DOI: 10.2967/jnumed.111.100545
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Imaging of Endogenous Pancreatic β-Cell Mass in Healthy and Type 1 Diabetic Subjects Using 18F-Fluoropropyl-Dihydrotetrabenazine and PET

Abstract: The ability to non-invasively measure endogenous pancreatic β-cell mass (BCM) would accelerate research on the pathophysiology of diabetes and revolutionize the preclinical development of new treatments, the clinical assessment of therapeutic efficacy, and the early diagnosis and subsequent monitoring of disease progression. The vesicular monoamine transporter type 2 (VMAT2) is co-expressed with insulin in β-cells and represents a promising target for BCM imaging. Methods We evaluated the VMAT2 radiotracer 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
101
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(107 citation statements)
references
References 34 publications
6
101
0
Order By: Relevance
“…To date, no other radiotracer tested for BCM determination has shown such large maximum differences between healthy individuals and patients with type 1 diabetes, nor has such a high interindividual variability of the uptake been reported previously [37][38][39][40][41][42][43][44]. A recent study in healthy individuals and patients with type 1 diabetes, involving PET after injection of [ 18 F]fluoropropyl-dihydrotetrabenazine ([ 18 F]FP-(+)-DTBZ), showed a maximum difference in pancreatic uptake of <40% [45]. The difference in binding potential between patients with type 1 diabetes and healthy individuals was not greater than 50% [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, no other radiotracer tested for BCM determination has shown such large maximum differences between healthy individuals and patients with type 1 diabetes, nor has such a high interindividual variability of the uptake been reported previously [37][38][39][40][41][42][43][44]. A recent study in healthy individuals and patients with type 1 diabetes, involving PET after injection of [ 18 F]fluoropropyl-dihydrotetrabenazine ([ 18 F]FP-(+)-DTBZ), showed a maximum difference in pancreatic uptake of <40% [45]. The difference in binding potential between patients with type 1 diabetes and healthy individuals was not greater than 50% [45].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in healthy individuals and patients with type 1 diabetes, involving PET after injection of [ 18 F]fluoropropyl-dihydrotetrabenazine ([ 18 F]FP-(+)-DTBZ), showed a maximum difference in pancreatic uptake of <40% [45]. The difference in binding potential between patients with type 1 diabetes and healthy individuals was not greater than 50% [45]. Moreover, a recent publication showed that expression of vesicular monoamine transporter 2 (VMAT2) in pancreatic polypeptide cells causes overestimation of the BCM in type 1 diabetes, as determined by PET measurements [46].…”
Section: Discussionmentioning
confidence: 99%
“…5A and B). Noninvasive imaging of pancreatic b-cell mass and function has been applied in normal and diabetic patients (Normandin et al 2012), but the accuracy of this approach needs to be further evaluated. The ratio of b-cells to non-b endocrine cells was unchanged after RYGB in the present study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, quantification of β-cell mass in vivo is relatively difficult due to the lack of reliable and noninvasive biomarkers for cells (24). Recently, the use of in vivo imaging techniques including positron-emission tomography (PET) and single-photon emission computed tomography (SPECT) with isotope-labeled ligands [such as In-labeled exendin] have been utilized in the field of human β-cell image studies (25)(26)(27). Likewise, BLI has been widely used with luciferase transgenic mice to evaluate β-cell mass under both normal and pathological conditions (17,28).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…In-labeled exendin] have been utilized in the field of human β-cell image studies (25)(26)(27). Likewise, BLI has been widely used with luciferase transgenic mice to evaluate β-cell mass under both normal and pathological conditions (17,28).…”
Section: F-fluoropropyl-(+)-dtbz and 111mentioning
confidence: 99%